Chemical cleaning of potable water membranes: The cost benefit of optimisation - Porcelli, Nicandro; Judd, Simon J. (Elsevier, 2010)
A study of the variability in chemical cleaning factors on permeability recovery for potable water microfiltration (MF) and ultrafiltration (UF) systems has been carried out employing a cost model simulating plant fouling and cleaning regimes. The impact of a range of operating and cleaning factors on operating cost variation was computed using algorithms describing operational and cleaning factor relationships with permeability recovery data measured from bench scale tests on fibres sampled from full-scale operational plants. The model proceeded through sequencing of the cleaning and backwashing operations to generate transmembrane pressure (TMP), and so head loss, transients. A number of cleaning scenarios were considered for each plant, based on employing either a threshold TMP or fixed chemical cleaning intervals. The resulting TMP profiles were then converted to operational costs. The effect of the variability in permeability recovery on annual operating costs was calculated for each of the simulations. It was evident that significant operating cost reductions were possible from optimisation of the cleaning protocol. Cost benefit varied according to facets of plant design and operation; the innate variability in permeability recovery precluded the correlation of cleaning efficacy with fouling characteristics.
Keywords: Membrane cleaning; Factorial analysis; Hollow fibre; Potable water; Cost benefit